2022
DOI: 10.1007/s11096-022-01455-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a post-discharge pharmacist opioid review following total knee arthroplasty: a pre- and post-intervention cohort study

Abstract: Background More than 70% of patients continue to use opioid medications 3-weeks following total knee arthroplasty. Post-discharge pharmacist reviews improve medication management, however it’s effect on opioid usage is not known. Aim This study aimed to evaluate the impact of post-discharge pharmacist review on opioid use following a total knee arthroplasty. Method A pilot, cohort pre- and post-intervention study was undertaken on patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…27 In a separate study at an Australian hospital, post-discharge review by a pharmacist was found to reduce the proportion of patients taking opioids three weeks following discharge. 28 In another Australian study, pharmacist-led, inpatient opioid de-escalation demonstrated a significant reduction in opioid use and constipation without adversely affecting patient-reported pain control. 29 In the United Kingdom and the United States of America, implementation of pharmacist prescribing improved opioid risk management and de-escalation.…”
Section: Evidence Of Pharmacist Impact On Pain Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…27 In a separate study at an Australian hospital, post-discharge review by a pharmacist was found to reduce the proportion of patients taking opioids three weeks following discharge. 28 In another Australian study, pharmacist-led, inpatient opioid de-escalation demonstrated a significant reduction in opioid use and constipation without adversely affecting patient-reported pain control. 29 In the United Kingdom and the United States of America, implementation of pharmacist prescribing improved opioid risk management and de-escalation.…”
Section: Evidence Of Pharmacist Impact On Pain Managementmentioning
confidence: 99%
“…Further, pharmacist review of discharge prescriptions from surgical wards has been shown to reduce the proportion of patients supplied with opioids 27 . In a separate study at an Australian hospital, post‐discharge review by a pharmacist was found to reduce the proportion of patients taking opioids three weeks following discharge 28 . In another Australian study, pharmacist‐led, inpatient opioid de‐escalation demonstrated a significant reduction in opioid use and constipation without adversely affecting patient‐reported pain control 29 .…”
Section: Evidence Of Pharmacist Impact On Pain Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent statement, the American Academy of Orthopaedic Surgeons stressed the need for a comprehensive opioid program to reduce opioid use, misuse, and abuse in the United States 13 . They specifically emphasized the importance of collaboration among all physicians and caregivers to ensure the safest and most effective treatment and management of pain 2,14,15 . This review aimed to describe a practical interdisciplinary approach for 1) screening and identifying at-risk patients and 2) providing appropriate interventions to opioid-treated patients undergoing orthopaedic surgery.…”
mentioning
confidence: 99%